Breast cancer prevalence and screening uptake among 1.46 million women in Inner Mongolia, China - Rui Guo; Cheng Tan; Yuxuan Gou; Jinling Shi; Fei Wang; Yibo Wu (The Lancet Regional Health. Western Pacific)
Background: While disparities in breast cancer prevalence between urban and rural areas have been widely studied in China, economically underdeveloped regions such as Inner Mongolia remain under-researched. As an autonomous region with significant economic challenges, including industrial reliance and environmental health risks, Inner Mongolia exemplifies the intersection of socioeconomic disadvantage and health inequalities. This study aims to explore breast cancer prevalence and screening uptake in Inner Mongolia, focusing on the disparities in early detection services among different socioeconomic groups. Methods: Data from the China Psychological and Behavioral Impact Survey (PBICR) and its breast cancer screening subset were analyzed, covering 1,459,868 women across 12 cities in Inner Mongolia from 2022 to 2024. Variables included demographics, behavioral factors, and family cancer history. Chi-square tests were used to examine differences in screening methods and prevalence across regions. Binary and ordinal logistic regression models identified factors influencing screening comprehensiveness, with a focus on the barriers faced by economically disadvantaged women. Findings: Among the women surveyed, 786 cases of breast cancer were reported, yielding a prevalence rate of 0.05%, consistent with the national average. The highest incidence was observed among women aged 40-50 years. Significant disparities in screening participation and methods were found (e.g., physical exams [χ2 = 1087.8, P < 0.001], ultrasounds [χ2 = 97.276, P < 0.001], X-ray exams [χ2 = 12643, P < 0.001], and pathological exams [χ2 = 219.81, P < 0.001]). Women from poverty-stricken households were less likely to receive comprehensive screening (β = -0.03, 95% CI: [-0.0377, -0.0193], P < 0.001), while younger women (β = -0.06, 95% CI: [-0.0679, -0.0493], P < 0.001) and those with higher education levels (primary school or below: β = -0.75, 95% CI: [-0.7678, -0.7337], university or above: β = 0.323, 95% CI: [0.3163, 0.3300], P < 0.001) were more likely to opt for multiple screening methods. Geographical disparities were also evident, with rural areas exhibiting lower participation rates and more limited access to advanced screening technologies. Interpretation: This study highlights significant health inequalities in breast cancer screening in Inner Mongolia, where economic hardship and geographical isolation disproportionately hinder access to early detection services. The findings suggest that policy interventions should prioritize economically underdeveloped regions to reduce health disparities and promote equitable healthcare access. Theoretically, this study underscores the importance of considering regional economic disparities in health inequality research, extending the current literature’s focus beyond urban-rural divides to encompass broader socioeconomic dimensions.